Formation of ultra-shallow p+/n junctions in silicon-on-insulator (SOI) substrate using laser annealing - Wang, X. C. (2013)
Laser annealing (LA), in which the laser melts the surface layer of silicon and causes the dopants to be distributed uniformly within the melted region, produces abrupt, highly activated and ultrashallow junctions. The degree of melting is determined by the extent of laser absorption and rate of heat dissipation, which are dependent on the substrate properties. When applying LA on substrates such as silicon-on-insulator (SOI), the heating and cooling characteristics are expected to be different from that of a typical Si substrate. This work compares the redistribution of boron atoms in silicon (1 0 0) and SOI substrates after laser annealing. SIMS analysis shows that laser induced melting is significantly deeper for the SOI than the silicon substrates using the same laser fluence. The enhancement of melting is attributed to the heat insulating effect of the buried oxide (BOX) layer. With multiple-pulse LA, the junction depth in the SOI substrate increases with subsequent laser pulses, a feature that is absent in silicon substrate. In the SOI substrate, the sheet resistance remains relatively constant regardless of deeper junction formed with multiple pulse conditions, implying the maximum dopant activation at a given laser fluence is reached. Boron profiles annealed in the non-melt regime with 20 laser pulses or less overlap with the as-implanted profiles, suggesting that no melting has occurred. However, significant melting is observed at 50-pulse annealing. The corresponding sheet resistance shows a sharp decrease with the initial pulses and consequently decreases slightly with increasing pulses.